Healthy aging interventions: exploring community partnerships to support Indigenous well-being - LeVatte, Lynn; Aldiabat, Khaldoun M. (Innovation in Health for Society, 2025)
A program named ‘Walking Our Way to Wellness’ was a healthy aging intervention developed and implemented in a rural Indigenous community. Focusing on interventions are valued and connected through both cultural and community models. This project emphasized the intergenerational aspects of health interventions. The research aimed to explore healthy aging practices, prevalent health conditions, health needs, and the impacts of a community partnership model involving a local post-secondary institution in Nova Scotia. This qualitative study included 17 participants who completed semi-structured interviews about their health and well-being. The mean age of the sample was 67 years, with 11 participants residing within the Indigenous community. A series of health interventions were developed based on participants' needs and interests through a community partnership involving a local Indigenous community, Cape Breton University Education Department, and the School of Nursing. These interventions included nutrition education, diabetes education, a walking program, and functional fitness programming. The results revealed that arthritis and diabetes were the most commonly reported health conditions among participants. Participants also noted their engagement in new functional fitness exercises and expressed that social interactions and scheduled classes were beneficial for their overall well-being. Suggestions for future research are also provided, which aim to build on the successes of this intervention and further explore the benefits of culturally grounded, community-driven health initiatives. Keywords: Aging, health condition, innovation in community health, nursing, partnership